PERAN KEPEMIMPINAN KEPALA SEKOLAH MEMODERASI PENGARUH KOMITMEN DAN KOMPETENSI TERHADAP KINERJA GURU SD DI KABUPATEN BATANG (Studi pada Guru SD di Kabupaten Batang) - Muhammad Arief Rohman, 11.52.02.0008 (Students Journal of Economic and Management, 2013)
This study to examine and analisys whether the role of headmaster leadership moderated influence commitment and competence on teacher performance. The study population was a primary school teacher of Batang Regency many as 3.330 people and a sample of 420 respondents. The research data is the primary data collected directly from the respondents to the questionnaire. The research method approach with computer software SPSS for Windows version 16. The method of data analysis using Moderation Regression analisys (MRA) type quasi moderator. The results of this study shows an interesting empirical conditions to be further investigated as follows: the original partially committed no significant effect on teachers performance, but after interacting with the headmaster leadership, the role of headmaster leadership to strengthen the influence ofÂ  commitment on teacher performance. Contrary, the original partially competence significant and positive effect on teacher performance, but after interacting with the headmaster leadership, the role of headmaster leadership to weaken influence of competence on teacher performance. Â  Keywords: commitment, competence, headmaster leadership, teacher performance